Conductivity and dielectric behavior studies on solid polymer electrolyte based poly(methyl methacrylate) (PMMA) grafted natural rubber (MG49) polymer blends - Shuhib Mamat,; Halim Haji Razali,; Kamaruzzaman Sopian,; Lee, Tian Khoon; Azizan Ahmad,; Matsumi, Noriyoshi; Mohd Sukor Su’ait, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A series of solid polymer electrolyte films, employing 49% poly(methyl methacrylate)(PMMA)-grafted natural rubber (MG49) as polymer host and lithium tertrafluoroborate (LiBF4 ) as conducting material were prepared by solution casting technique. The films of MG49-LiBF4 , MG49-PMMA and MG49-Poly(vinylidene fluoride-co-hexafluoropropylene)(PVDF-HFP) at the optimum weight percentage of LiBF4 (25 wt.%, 25 wt.% and 30 wt.%) respectively, were characterized using potentiostatic electrochemical impedance spectroscopy (EIS) technique to measure their impedans. The measurements were conducted at the temperature range from 303 K to 403 K. The values of dielectric constant, Ꜫr increases with the increase of ionic conductivity. The dielectric constant, Ꜫr and dielectric loss, Ꜫi decrease with increase in frequency at the low frequency region attributed to the electrode polarization effects, but almost negligible in the high frequency region due to frequency independent. The imaginary part, Mi of electrical modulus are observed increases with frequency. The systems are concluded as ionic conductors by the present of Mi peak in the plot Mi versus frequency. The presence of peaks at certain frequency in the tan δ versus frequency plots of the polymer electrolytes indicate the existence of relaxation of charge in all samples contributed by the ions and polar functional groups.